(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The growth of solid crystalline forms, or stones, in the urinary tract is referred to as urolithiasis, also known by the name’s kidney stones and urinary calculi. Several plants that are believed to have medicinal properties have been used in traditional medicine to treat various conditions. Many cultures have employed these medicines because of their ability to prevent, treat, or decrease kidney stone symptoms. When plants are used to treat urolithiasis, they often cure multiple aspects of the condition, including diuresis (increased urine production), prevention of crystal formation, and assistance in dissolving or removing existing stones. While anecdotal evidence and conventional wisdom may provide support to their use, thorough scientific investigation is necessary to validate them and ascertain their safety and effectiveness. Based on the results of the ethnobotanical survey, Abutilon indicum (L.) Sweet, Ouretlanata (L.) Kuntze, and Tribulus terrestris L. were selected for the current study with this objective in mind. Phenols were detected in all samples after a phytochemical screening of the leaves of Tribulus terrestris L., Ouretlanata (L.) Kuntze, and Abutilon indicum (L.). Methanolic extracts showed the highest concentration of phenols. Naturally occurring antioxidants such tannin, total phenols, flavanoids, vitamin C, and vitamin E were also investigated. Tribulus terrestris had higher antioxidant levels than Ouretlanata and Abutilon indicum. These plants had substantially higher levels of flavonoids than other antioxidants because they have a better capacity to catalyse urolithiasis.